2007
DOI: 10.1128/jcm.02343-06
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans Clonal Variation Revealed by Multilocus Sequence Typing

Abstract: Streptococcus mutans is the major pathogen of dental caries, a biofilm-dependent infectious disease, and occasionally causes infective endocarditis. S. mutans strains have been classified into four serotypes (c, e, f, and k). However, little is known about the S. mutans population, including the clonal relationships among strains of S. mutans, in relation to the particular clones that cause systemic diseases. To address this issue, we have developed a multilocus sequence typing (MLST) scheme for S. mutans. Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
134
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(156 citation statements)
references
References 43 publications
15
134
7
Order By: Relevance
“…We found that the distribution of the cnm gene in S. mutans from Thai subjects was highest in serotype f (54.5 %). Such distribution was also observed in S. mutans strains from Japanese and Finnish people (Nakano et al, 2007;Nomura et al, 2009). These results thus confirmed the association between serotype f and the presence of the cnm gene in S. mutans.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We found that the distribution of the cnm gene in S. mutans from Thai subjects was highest in serotype f (54.5 %). Such distribution was also observed in S. mutans strains from Japanese and Finnish people (Nakano et al, 2007;Nomura et al, 2009). These results thus confirmed the association between serotype f and the presence of the cnm gene in S. mutans.…”
Section: Discussionsupporting
confidence: 76%
“…Equal numbers of S. mutans strains without the cnm gene in each serotype were also subjected to MLST as the control strains for the Thai subjects. Briefly, internal fragments of eight housekeeping gene loci were amplified (Nakano et al, 2007), and their nucleotide sequences determined (Table 1). The sequences for each housekeeping gene fragment were compared with the previously described data (Lapirattanakul et al, 2008;Nakano et al, 2007) in order to assign et al, 2001) were used to produce a matrix of pairwise differences in the allelic profiles and a dendrogram was constructed from the matrix using UPGMA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…75% of isolates, typically lack the cnm locus. [21][22][23][24] Intriguingly, the less abundant serotypes are highly overrepresented among isolates associated with S. mutans extra-oral infections. 25,26 This disparity in distribution provided some of the first evidence that such collagen-binding adhesins may make a critical contribution to the capacity for S. mutans to cause systemic disease.…”
mentioning
confidence: 99%